The Uptake and Release of Amino Acids by Staphylococcus aureus at Mid-Exponential and Stationary Phases and Their Corresponding Responses to Changes in Temperature, pH and Osmolality - Alreshidi, Mousa M.; Dunstan, R. Hugh; Macdonald, Margaret M.; Gottfries, Johan; Roberts, Tim K. (Frontiers in Microbiology, 2020)
Staphylococcus aureus is an important pathogen that is associated with nosocomial infections, as well as food poisoning. This bacterium is resistant to antimicrobial agents and can survive in a wide range of environmental conditions. The aim of this study was to measure the uptake and release of amino acids by S. aureus at mid-exponential and stationary phases of growth following exposure to a combination of conditions including variations in temperature, pH and NaCl. Bacterial cells were grown up to mid-exponential and stationary phases in tryptic soy broth (TSB), where the supernatants were collected for analyses of amino acids to determine the uptake and release characteristics. The uptake/release of amino acids was estimated by subtracting the initial levels of the free amino acids in the media from those measured at mid-exponential and stationary phases of growth. When cells were grown at ideal conditions, the analyses revealed that significant uptake of amino acids had occurred by stationary phase compared with the mid-exponential phase. A substantial release of valine and tyrosine into the external media was observed by cells at stationary phase. At both phases, the uptake and release patterns were significantly different between cells grown under ideal control conditions, when compared with those grown under various combinations of sub-optimal environmental conditions. The analyses of the supernatants harvested from controls and treatment groups at exponential phase indicated that the total uptake of amino acids was reduced approximately five times by cells grown with addition of 2.5% NaCl or with pH6 at 35°C, and two-fold by cells grown at pH8 at 35 °C. However, the final quantities of amino acids taken up by cells grown to stationary phase did not significantly alter between control and treated samples. Valine was found to be the most abundant amino acid that was significantly released into the media at stationary phase by both control and treated samples. It was evident that diverse environmental conditions resulted in differential patterns of amino acid uptake and release during adaptation to designated conditions.